Tooth Loss Increases the Risk of Diminished Cognitive Function: A Systematic Review and Meta-analysis. (April 2016) - Cerutti-Kopplin, D.; Feine, J.; Padilha, D.M.; de Souza, R.F.; Ahmadi, M.; Rompré, P.; Booij, L.; Emami, E.
Emerging evidence suggests that oral health is associated with cognitive function. This review aims to systematically assess this association in adult populations via prospective cohort study designs. Eligible study reports were identified by searching the MEDLINE (via Ovoid), EMBASE, PsycoINFO, and Cochrane Library databases. Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated with a random effects model. From 1, 251 identified articles, 10 were included in the systematic review and 8 in the meta-analysis. Random effects analysis showed, with statistically low heterogeneity, that individuals with suboptimal dentition (<20 teeth) were at a 20% higher risk for developing cognitive decline (HR = 1.26, 95% CI = 1.14 to 1.40) and dementia (HR = 1.22, 95% CI = 1.04 to 1.43) than those with optimal dentition (≥20 teeth). Studies on the association between periodontal disease and cognitive status showed conflicting results. Within the limits of the quality of published evidence, this meta-analysis lends further support to the hypothesis that tooth loss is associated with an increased risk of cognitive impairment and dementia. Knowledge Transfer Statement : Based on the published literature, the results of this study show that the risk for cognitive impairment and dementia increases with loss of teeth. This information adds to the evidence showing links between oral and general health and suggests that oral health strategies aimed to preserve teeth may be important in reducing risk of systemic disease.